EFFECTIVE METHODS OF ENGLISH TEACHING IN HIGHER EDUCATION - Maftuna Akhmadova (PEDAGOGS, 2024)
Annotation. This article explores various methods of teaching English in higher education, focusing on their effectiveness and applicability. The study examines traditional and contemporary approaches, incorporating technology, interactive activities, and learner-centered strategies. It aims to provide educators with insights and practical recommendations for enhancing English language instruction at the tertiary level.